A retrospective population-based cohort study identifying target areas for prevention of acute lower respiratory infections in children - Richmond Peter; de Klerk Nicholas; Moore Hannah C; Lehmann Deborah (BMC, 2010)
Abstract Background Acute lower respiratory infections (ALRI) are a major cause of hospitalisation in young children. Many factors can lead to increased risk of ALRI in children and predispose a child to hospitalisation, but population attributable fractions for different risk factors and how these fractions differ between Indigenous and non-Indigenous children is unknown. This study investigates population attributable fractions of known infant and maternal risk factors for ALRI to inform prevention strategies that target high-risk groups or particular risk factors. Methods A retrospective population-based data linkage study of 245,249 singleton births in Western Australia. Population attributable fractions of known maternal and infant risk factors for hospitalisation with ALRI between 1996 and 2005 were calculated using multiple logistic regression. Results The overall ALRI hospitalisation rate was 16.1/1,000 person-years for non-Aboriginal children and 93.0/1,000 for Aboriginal children. Male gender, being born in autumn, gestational age <33 weeks, and multiple previous pregnancies were significant risk factors for ALRI in both Aboriginal and non-Aboriginal children. In non-Aboriginal children, maternal smoking during pregnancy accounted for 6.3% (95%CI: 5.0, 7.6) of the population attributable fraction for ALRI, being born in autumn accounted for 12.3% (10.8, 13.8), being born to a mother with three or more previous pregnancies accounted for 15.4% (14.1, 17.0) and delivery by elective caesarean accounted for 4.1% (2.8, 5.3). In Aboriginal children, being born to a mother with three or more previous pregnancies accounted for 16.5% (11.8, 20.9), but remote location at birth accounted for 11.7% (8.5, 14.8), maternal age <20 years accounted for 11.2% (7.8, 14.5), and being in the most disadvantaged socio-economic group accounted for 18.4% (-6.5, 37.4) of the population attributable fraction. Conclusions The population attributable fractions estimated in this study should help in guiding public health interventions to prevent ALRI. A key risk factor for all children is maternal smoking during pregnancy, and multiple previous pregnancies and autumnal births are important high-risk groups. Specific key target areas are reducing elective caesareans in non-Aboriginal women and reducing teenage pregnancies and improving access to services and living conditions for the Aboriginal population.